Functional Capacity in Adults With Cerebral Palsy: Lower Limb Muscle Strength Matters - Gillett, J.; Lichtwark, G.; Boyd, Roslyn; Barber, L. (W.B. Saunders Co., 2018)
Objective: To investigate the relation between lower limb muscle strength, passive muscle properties, and functional capacity outcomes in adults with cerebral palsy (CP). Design: Cross-sectional study. Setting: Tertiary institution biomechanics laboratory. Participants: Adults with spastic-type CP (N=33; mean age, 25y; range, 15–51y; mean body mass, 70.15±21.35kg) who were either Gross Motor Function Classification System (GMFCS) level I (n=20) or level II (n=13). Interventions: Not applicable. Main Outcome Measures: Six-minute walk test (6MWT) distance (m), lateral step-up (LSU) test performance (total repetitions), timed up-stairs (TUS) performance (s), maximum voluntary isometric strength of plantar flexors (PF) and dorsiflexors (DF) (Nm.kg -1 ), and passive ankle joint and muscle stiffness. Results: Maximum isometric PF strength independently explained 61% of variance in 6MWT performance, 57% of variance in LSU test performance, and 50% of variance in TUS test performance. GMFCS level was significantly and independently related to all 3 functional capacity outcomes, and age was retained as a significant independent predictor of LSU and TUS test performance. Passive medial gastrocnemius muscle fascicle stiffness and ankle joint stiffness were not significantly related to functional capacity measures in any of the multiple regression models. Conclusions: Low isometric PF strength was the most important independent variable related to distance walked on the 6MWT, fewer repetitions on the LSU test, and slower TUS test performance. These findings suggest lower isometric muscle strength contributes to the decline in functional capacity in adults with CP.